Unravelling potential virulence factor candidates in Xanthomonas citri. subsp citri by secretome analysis - Ferreira, Rafael M. [UNESP]; Moreira, Leandro M.; Ferro, Jesus A. [UNESP]; Soares, Marcia R. R.; Laia, Marcelo L.; Varani, Alessandro M. [UNESP]; Oliveira, Julio C. F. de; Ferro, Maria Ines T. [UNESP] (Peerj Inc, 2016)
Citrus canker is a major disease affecting citrus production in Brazil. It's mainly caused by Xanthomonas citri subsp. citri strain 306 pathotype A (Xac). We analysed the differential expression of proteins secreted by wild type Xac and an asymptomatic mutant for hrpB4 (Delta hrpB4) grown in Nutrient Broth (NB) and a medium mimicking growth conditions in the plant (XAM1). This allowed the identification of 55 secreted proteins, of which 37 were secreted by both strains when cultured in XAMI. In this secreted protein repertoire, the following stand out: Virk, Polyphosphate-selective porin, Cellulase, Endoglucanase, Histone-like protein, Ribosomal proteins, five hypothetical proteins expressed only in the wild type strain, Lytic murein transglycosylase, Lipoprotein, Leucyl-tRNA synthetase, Co-chaperonin, Toluene tolerance, C-type cytochrome biogenesis membrane protein, Aminopeptidase and two hypothetical proteins expressed only in the Delta hrpB4 mutant. Furthermore, Peptidoglycan-associated outer membrane protein, Regulator of pathogenicity factor, Outer membrane proteins, Endopolygalacturonase, Chorismate mutase, Peptidyl-prolyl cis-trans isornerase land seven hypothetical proteins were detected in both strains, suggesting that there was no relationship with the secretion mediated by the type III secretory system, which is not functional in the mutant strain. Also worth mentioning is the Elongation factor Tu (EF-Tu), expressed only the wild type strain, and Type IV pilus assembly protein, Flagellin (FliC) and Flagellar hook-associated protein, identified in the wild-type strain secretome when grown only in NB. Noteworthy, that FliC, EF-Tu are classically characterized as PAMPs (Pathogen-associated molecular patterns), responsible for a PAMP-triggered immunity response. Therefore, our results highlight proteins potentially involved with the virulence. Overall, we conclude that the use of secretome data is a valuable approach that may bring more knowledge of the biology of this important plant pathogen, which ultimately can lead to the establishment of new strategies to combat citrus canker.
Keywords: Plant pathogen interaction; Medium inducing pathogenicity; Type III secretion system; Virulence; Asymptomatic mutant; Type II secretion system; Secretomics